2021
DOI: 10.3389/fmicb.2021.731764
|View full text |Cite
|
Sign up to set email alerts
|

Tomato Endophytic Bacteria Composition and Mechanism of Suppressiveness of Wilt Disease (Fusarium oxysporum)

Abstract: Tomato wilt disease, caused by the Fusarium oxysporum is an ever-increasing threat for agricultural production, and unreasonable fertilization and pesticide abuse caused environmental challenge. Increasing evidence suggested that microbiomes or those associated with crops, played key roles on plant health. Plant disease dynamics were affected by multiple biotic and abiotic factors including phytopathogen population density, the genetic type of the pathogen and the host, in particular, the composition and assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…The enriched OTUs of healthy plants probably play an important role in protecting the plants from cotton Verticillium wilt. This finding is consistent with the previous report ( Yuan et al, 2020 ; Zhang et al, 2021 ). Furthermore, the results displayed that the healthy plants and resistant cultivars contained specific OTUs corresponding to Sphingobacteriaceae, which included the biocontrol genus of Sphingobacterium ( Xu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…The enriched OTUs of healthy plants probably play an important role in protecting the plants from cotton Verticillium wilt. This finding is consistent with the previous report ( Yuan et al, 2020 ; Zhang et al, 2021 ). Furthermore, the results displayed that the healthy plants and resistant cultivars contained specific OTUs corresponding to Sphingobacteriaceae, which included the biocontrol genus of Sphingobacterium ( Xu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…The number of links among members within a fungal community increased soon after the Ggt application, but decreased significantly later on, while strain Z-14 significantly increased the fungal community interactions (Table 3). Pathogen invasion significantly disrupted microbial associations when compared with the healthy tomato whose microbial associations were more complex (Zhang et al, 2021). In our study, more positive interactions were found with the inoculation of strain Z-14, indicating that synergies among microbes were enhanced.…”
Section: Effects Of Bacillus Subtilis Z-14 On Wheat Rhizospheric Fung...mentioning
confidence: 48%
“…Endophytic bacteria also play an important role in promoting plant growth. Moreover, endophytic bacteria can effectively enhance disease control ( 37 ). In this study, even though soil bacterial diversity and richness in the rhizosphere were not significantly different between netted and oriental melons, the endophytic bacterial diversity and richness in the stems of netted melons were significantly higher than those of oriental melons.…”
Section: Discussionmentioning
confidence: 99%